Sportkardiologie - Löllgen H (Dynamic Media Sales Verlag, 2017)
Within the last twelve years, many consensus conferences and working groups have reported new recommendations for ECG interpretation in endurance exercise athletes. New data have improved validity and reliability of resting ECG in athletes, reducing especially false positive findings. In particular, these new recommendations classify ECG signs of hypertrophy and enlargement of ventricles or atria, or axis deviation in isolation as borderline findings. Conversely, signs of hypertrophy or enlargements associated with other abnormal findings require further evaluation. In addition, procedures for the diagnostic evaluation of abnormal findings are described in detail. With this recommendation, the reliability of the resting ECG is superior to anamnesis and clinical examination in the recognition of abnormal findings, and should be a mandatory part of pre-participation examination for all athletes. Even though the reliability is supported by integrated PC-assisted ECG analysis, special cardiological knowledge in ECG interpretation is required. Therefore, special education in sports cardiology is strongly recommended for all qualified sports physicians.KEY WORDS: ECG, Interpretation, Consensus, Athletes, ECG Device